PENGUNGKAPAN NILAI PERSAHABATAN ANTARA BEN DAN JODY MELALUI SEMANTIK – DIALOG FILOSOFI KOPI - Reza Pahlevi Ginting (JURNAL CURERE, 2018)
Film Filosofi Kopi (2015) tells the story of a coffee farm boy who since childhood he grew up on a coffee plantation he named Ben (Chico Jericho). However, at the age of 12 years, Ben went to leave his parents until he met with Jody (Rio Dewanto) and both were immediately familiar and they were good friends. The research design used by writer is literature study method (qualitative). In this study, researchers collect data by recording based on the dialogue contained in the film and the methods used in collecting data is the method of referring (Sudaryanto, 1993: 133). The technique used in this method, namely Techniques Free Libat Cawap. Data analysis is done by comprehending the story thoroughly, identifying and clarifying all data based on the subject matter, and concluding the result of data analysis so that it can be explained clearly. The results of this study, namely 1) The value of friendship that is perceptible in the film Filosofi Kopi, namely the existence of interdependence between Jody with Ben. Dependence exists in the form of mutual need, either emotionally as a friend or professionally between coffee shop entrepreneurs with the most reliable coffee makers.